Removal of Lead from Polluted Water Using Corn Silk As a Cheap Biosorbent - Yaghoub Karimi; Safar Marofi; Mohamad Ali Zare (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Entry of heavy metals into water resources has harmful effects on human health and the environment. In recent years, adsorption methods using natural absorbents to remove contaminants from water resources have been used abundantly. Corn silk as a biosorbent can be effective for the removal of lead ions from aquatic solutions. The purpose of this research was to remove lead by corn silk as a cheap biosorbent from polluted water in vitro. Methods: The effects of variables such as pH, contact time, initial concentration, adsorbent amount, and efficiency in removing lead from contaminated water were studied. Isotherms of Langmuir, Freundlich and Temkin were fitted with the data of the experiment. In addition, kinetics of pseudo first order, pseudo second order, intra-particle diffusion, and Elovich were fitted with the experimental data. Graphs and data analyses were performed using Excel program. Results: For corn silk, Langmuir isotherms showed good agreement with the experimental data. Using these models, maximum absorption capacity of 78.84 (mg.g-1) was obtained for corn silk. Absorption kinetics showed quick responses in less than one hour. The results showed that the adsorption kinetics of pseudo second order was more consistent for lead pollutant (r2=0.99). Conclusion: The results demonstrated that corn silk absorbent is effective in removing lead contaminants from aqueous solutions due to high surface area, having SiOH groups, high absorption capacity, and rapid kinetics of reaction. Therefore, the use of this adsorbent is recommended to remove lead from aqueous solutions.